Moderating Role of Firm Size in the Relationship between Profitability, Leverage, and Stock Returns: Evidence from Indonesian Agriculture Sector - Maria, Evi; Sudiarto, Edi (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study explores the effect of Return on Assets (ROA) and Debt to Equity Ratio (DER) on stock returns, with firm size as a moderating variable in agricultural companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2021. Methodology: Using a quantitative approach and purposive sampling, 20 firms were analyzed over four years. Data were tested through classical assumption tests, hypothesis testing, and Moderated Regression Analysis (MRA). Results: ROA significantly and positively affects stock returns, while DER shows no direct impact. Firm size does not moderate the ROA–stock return relationship but does moderate the DER–stock return relationship. Findings: Profitability enhances investor value regardless of company size. However, the influence of leverage on stock returns varies depending on firm size. Novelty: This study highlights firm size as a conditional factor, offering new insights into its role in financial performance within Indonesia’s agricultural sector. Originality: Unlike prior research, firm size is treated as a moderator, not merely a control variable, revealing its strategic relevance. Conclusion: Company size selectively moderates financial indicators, emphasizing its importance in evaluating market performance. Type of Paper: Empirical research.